2019
DOI: 10.1021/acs.jced.9b00229
|View full text |Cite
|
Sign up to set email alerts
|

Solubility Determination and Model Correlation of Pymetrozine and Evaluation of the Effect of Solvent Properties and Composition

Abstract: In this research, the purpose is to study the solid–liquid equilibrium solubility of pymetrozine and the influence of the solvent effect on solubility. The solubility of pymetrozine was measured by using a static equilibrium method. The solubility of pymetrozine increases with increasing temperature, and the solubility from high to low is dimethyl sulfoxide (DMSO, 0.8623 × 10–2, 298.15 K) > N,N-dimethylformamide (DMF, 0.5147 × 10–2, 298.15 K) > N-methyl pyrrolidone (NMP, 0.2946 × 10–2, 298.15 K) > 1,4-dioxane … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 24 publications
0
29
0
Order By: Relevance
“…In addition, although the solubility of l -alanine in polar protic solvents was higher than that in polar aprotic solvents, the order in the two kinds of solvents was both inconsistent with the polarity, dipole moment, dielectric constant, and solubility parameter orders (the solvent properties can be seen in Table ). This indicated that the dissolution equilibrium of l -alanine was a complex phenomenon, which may be attributed to the comprehensive influence of various factors, such as solvent properties, molecular sizes and shapes, solute–solvent interactions, solvent–solvent interactions, solute–solute interactions, steric effect, etc. From Figure b, there were some intersects between the solubility curves, which may result from the weight differences of the above factors under different temperatures. , …”
Section: Resultsmentioning
confidence: 95%
“…In addition, although the solubility of l -alanine in polar protic solvents was higher than that in polar aprotic solvents, the order in the two kinds of solvents was both inconsistent with the polarity, dipole moment, dielectric constant, and solubility parameter orders (the solvent properties can be seen in Table ). This indicated that the dissolution equilibrium of l -alanine was a complex phenomenon, which may be attributed to the comprehensive influence of various factors, such as solvent properties, molecular sizes and shapes, solute–solvent interactions, solvent–solvent interactions, solute–solute interactions, steric effect, etc. From Figure b, there were some intersects between the solubility curves, which may result from the weight differences of the above factors under different temperatures. , …”
Section: Resultsmentioning
confidence: 95%
“…The KAT-LSER model proposed by Kamlet and co-workers has been widely used to express the Gibbs energy of solid–liquid phase equilibrium through the physical properties of both solute and solvent molecules. It was based on the linear contribution of several solute–solvent interactions to inspect the solvent effect on the solubility behavior, and the expression was given by eq . , …”
Section: Theoretical Sectionmentioning
confidence: 99%
“…The average relative deviation (ARD, eq ) and root-mean-square deviation (RMSD, eq ) were calculated to evaluate the applicability and the accuracy of the solubility models. In addition, Akaike information criterion (AIC) and Akaike weight (ω i ) values were calculated to further evaluate the relative applicability of these thermodynamic models. A detailed description of the symbols in all of the above formulas is given in Table .…”
Section: Solubility and Model Calculationmentioning
confidence: 99%